Historical Perspectives on Relations between Chama Cha Mapinduzi and the Communist Party of China (1965-1985). - Prah, Kwesi Dzapong Lwazi Sarkodee (African & Asian Studies, 2020)
Between the respective anti-colonial movements in mainland China and Tanzania and the independence that followed, the political, economic and scientific development that ensued required systematic planning and implementation. The relationship that developed between Chama Cha Mapinduzi (CCM) of Tanzania and the Communist Party of China (CPC) lay the foundation for what many regard as the proto-typical character and example of Chinese diplomacy and its influence in Africa, as well as how states and political parties interact with each other given certain global, geo-political challenges. This paper briefly outlines the main motivations, ideas, plans and implementation of the various exchanges and activities shared between the two political parties. It argues that the idea of party-to-party relations between China and Tanzania required a practical edge that prepared them for the global challenges they faced, and more importantly, prescribed the developmental nature of their relationship.